The Healing of Oxidative Injuries with Trehalose in UVB-Irradiated Rabbit Corneas - Cejka, Cestmir; Kossl, Jan; Hermankova, Barbora; Holan, Vladimir; Kubinova, Sarka; Olmiere, Céline; Cejkova, Jitka (Oxidative medicine and cellular longevity, 2019)
Our previous research revealed that trehalose, a nonreducing disaccharide of glucose and an important stress responsive factor, proved to have anti-inflammatory, antiapoptotic, and particularly antioxidant properties in UVB-irradiated corneas. Trehalose reduced oxidative stress in corneas induced by UVB irradiation, by means of a decrease in the antioxidant/prooxidant imbalance in the corneal epithelium. In this study, we demonstrate that trehalose of 3% or 6% concentration in eye drops directly decreases oxidative stress in UVB-irradiated corneas, by removing the excessive amount of reactive oxygen species (ROS). Trehalose drops applied on corneas during UVB irradiation once daily for four days resulted in a reduction or even absence of the oxidative stress, DNA damage, and peroxynitrite formation (detected by nitrotyrosine residues), seen in buffer-treated corneas. Furthermore, trehalose treatment applied curatively after repeated irradiation for the subsequent fourteen days led to the renewal of corneal transparency and significant suppression or even absence of neovascularization. This was in contrast to buffer-treated irradiated corneas, where the intracorneal inflammation was developed and the untransparent corneas were vascularized. In conclusion, the treatment of UVB-irradiated corneas with trehalose eye drops removed the excessive amount of ROS in the corneal epithelium, leading to the suppression of oxidative stress and favorable corneal healing. The 6% trehalose showed a higher intensive antioxidant effect.
Keywords: Animals; Trehalose; Rabbits; DNA Damage; synthasa oxidu dusnatého, typ II; Female; oxidační stres; Keratins; rohovka; ženské pohlaví; Wound Healing; vaskulární endoteliální růstový faktor A; Oxidative Stress; Cornea; Tyrosine; keratiny; Ultraviolet Rays; Reactive Oxygen Species; Vascular Endothelial Growth Factor A; Corneal Injuries; poškození DNA; Interleukin-1beta; hojení ran; Nitric Oxide Synthase Type II; reaktivní formy kyslíku; tyrosin; Re-Epithelialization; interleukin-1beta; králíci; zvířata; trehalosa; poranění rohovky; reepitalizace; ultrafialové záření